A problematic drinker in the family: Variations in the level of negative impact experienced by sex, relationship and living status - Berends, L.; Ferris, J.; Laslett, Anne-Marie (Informa Healthcare, 2012)
A national survey on harms experienced from others' drinking was administered by telephone to 2649 randomly selected adults (1898 years) in Australia. This article is about responses from participants concerning the family member whose drinking had the most negative impact on them (referred to as the problematic drinker). Respondents were asked about their relationship with the drinker, if they shared a household, and the level of negative impact they experienced. Of the 1494 family members identified as 'fairly heavy drinkers'/'drinking a lot sometimes', the drinking of 592 (39.6) had negatively affected 415 respondents in the previous 12 months. The problematic drinker was usually male (72.0) and a partner (22.2), child (18.2), or sibling (16.3). Most problematic drinkers in the home were partners (45.9) or children (23.5); there was no significant difference between problematic drinking sons living at home (62.0) compared with problematic drinking daughters (45.2). One-third of the respondents (35.8) were affected 'a lot' by the problematic drinker; of those affected a lot, 52.6 lived with the problematic drinker. Severity of impact was significantly associated with the living status of the drinker but not with the sex of the drinker. This population-based study shows negative effects are often experienced when people have a family member who drinks a lot. While partners are often involved, a substantial proportion of problematic drinkers are adult children or siblings.